SPE California Regional Meeting 1988
DOI: 10.2118/17423-ms
|View full text |Cite
|
Sign up to set email alerts
|

Correcting Oil/Water Relative Permeability Data for Capillary End Effect in Displacement Experiments

Abstract: Reproduced with permission of the copyright owner. Further reproduction prohibited without permission. A .l Data from capillary pressure experiments 88 A .2 Core # 1 1.0 cc/m in drainage displacement data 89 A.3 Core # 1 0.5 cc/m in drainage displacement data 91 A.4 Core # 2 2.0 cc/m in drainage displacement data 93 A .5 Core # 3 0.2 cc/m in drainage displacement data 95 A .6 Core # 1 1.0 cc/m in Imbibition displacement data 97 A .7 Core # 1 steady-state relative permeability data 99 Reproduced with permission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…This method assumes that the pressure drop measured during the experiment always represents the pressure drop across the wetting phase and the capillary effects influence only the non-wetting phase relative permeability. They based the latter assumption on the published data (Qadeer et al 1988). It has been demonstrated that capillary pressure affects both the wetting and non-wetting phase relative permeabilities (Civan and Donaldson 1989, Kalbus and Christiansen 1995, Qadeer 2001).…”
Section: Methodsmentioning
confidence: 99%
“…This method assumes that the pressure drop measured during the experiment always represents the pressure drop across the wetting phase and the capillary effects influence only the non-wetting phase relative permeability. They based the latter assumption on the published data (Qadeer et al 1988). It has been demonstrated that capillary pressure affects both the wetting and non-wetting phase relative permeabilities (Civan and Donaldson 1989, Kalbus and Christiansen 1995, Qadeer 2001).…”
Section: Methodsmentioning
confidence: 99%
“…The frontal saturation corresponds to the tangent point between the f-f curve and the straight line drawn from the point Si,the slope of this line is equal to the displacement front velocity D, The geometric interpretation of the continuous solution (12), (13) is: the saturation value corresponds to the value of self-similar coordinate which is equal to the slope of f-f curve in the point of this saturation. This allows for a graphic-analytical construction of the saturation profile (Fig, 1).…”
Section: I-d Coreflood In Large Scale Approximation: Buckley-leversttmentioning
confidence: 99%
“…This allows for a graphic-analytical construction of the saturation profile (Fig, 1). The solution (12), ( 13) is the outer asymptotic expansionmzz for the displacement problem honouring the capillary pressure.…”
Section: I-d Coreflood In Large Scale Approximation: Buckley-leversttmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, this approach may give stable results only for fixed analytical expressions of relative permeability (Batycky et al 1981;Richmond et al 1990;Qadeer et al 1988;Chardaire-Riviere et al 1992;Sigmund and Mccaffery 1979). Nevertheless, very different shapes of relative permeability have been reported in the literature (Honarpour et al 1986;Kerig and Watson 1986), which reduces the stability of the optimization method.…”
Section: Introductionmentioning
confidence: 99%